Humanitarian medicine : a compilation of the leading articles in the Journal of humanitarian medicine, 2000-2004 - Gunn, S. William; Masellis, Michele (International Association for Humanitarian Medicine Brock Chisholm, 2005)
The publication is a collection of articles which focus on humanitarian medinice, human rights, international cooperation and disasters. Intended for professional public.
Keywords: Relief Work; právo na zdraví; veřejné zdravotnictví; Disaster Medicine; pomoc v nouzi; lidská práva; medicína katastrof; mezinárodní spolupráce; International Cooperation; urgentní lékařství; Right to Health